2012
DOI: 10.1155/2012/175249
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Perceptions and Practices among Canadian Gastroenterologists regarding the Prevention of Venous Thromboembolism for Hospitalized Inflammatory Bowel Disease Patients

Abstract: There was a general consensus among academic gastroenterologists that IBD inpatients are at an increased risk for VTE and would benefit from VTE prophylaxis. However, areas of uncertainty still exist and the IBD community would benefit from evidence-based clinical practice guidelines to standardize the management of this important problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Low molecular weight heparin and fondaparinux have been shown to significantly reduce VTE risk in hospitalised patients . Despite the latter evidence, surveys indicate that up to 65% of gastroenterologists fail to administer VTE prophylaxis to patients admitted for ASUC . Thromboprophylaxis does not appear to precipitate excessive bleeding during flares of IBD, even in patients experiencing bloody diarrhoea, and is recommended in all patients with ASUC .…”
Section: Complications Associated With Asucmentioning
confidence: 99%
See 1 more Smart Citation
“…Low molecular weight heparin and fondaparinux have been shown to significantly reduce VTE risk in hospitalised patients . Despite the latter evidence, surveys indicate that up to 65% of gastroenterologists fail to administer VTE prophylaxis to patients admitted for ASUC . Thromboprophylaxis does not appear to precipitate excessive bleeding during flares of IBD, even in patients experiencing bloody diarrhoea, and is recommended in all patients with ASUC .…”
Section: Complications Associated With Asucmentioning
confidence: 99%
“…149 Despite the latter evidence, surveys indicate that up to 65% of gastroenterologists fail to administer VTE prophylaxis to patients admitted for ASUC. [150][151][152] Thromboprophylaxis does not appear to precipitate excessive bleeding during flares of IBD, even in patients experiencing bloody diarrhoea, and is recommended in all patients with ASUC. 153,154 The VTE risk in IBD patients appears to be highest in ambulant out-patients following discharge from hospital (HR 15.8; 95% CI: 9.8-25.5, P < 0.0001), suggesting that there may be a role for maintaining prophylaxis in the out-patient setting.…”
Section: Venous Thromboembolismmentioning
confidence: 99%
“…Despite evidence supporting an increased risk for VTE and its associated morbidity and mortality in IBD patients, there is significant variation in practice for VTE prophylaxis among gastroenterologists (16,17). A recent United States medical and drug insurance claims database review indicated that fewer than one-third of hospitalized IBD patients receive prophylactic anticoagulants (18).…”
Section: Designated Qis In Ibd Andmentioning
confidence: 99%
“…Several recent surveys document that management by IBD specialists differs widely, even when level 1 evidence, endorsed by national or international treatment guidelines, exists for a specific clinical problem. For example, a large variation exists in the use of prophylaxis for thromboembolic disease (TED) in hospitalized patients with IBD [14,15]. Compared to the general population, patients with IBD are three times as likely to develop TED.…”
Section: What Is Ebm?mentioning
confidence: 99%